(Identification of lime(Citrus aurantifolia,swingle)flavor components) - Ngakan Timur Antara; Enny Hawani Lubis (Balai Besar Industri Agro, 1995)
The research concerned with the effect of collecting time of the lime flavour distilate on the yield and composition of flavour components had been done succesfully.The collecting time has a significant effect not just to the yield obtained but to the flavour composition as well.In terms of the flavour compound,11 components had been identified namely-pinene,b-pinene,phellandrene,limonene,carryophyllene,decanal,neral,nerol,linalool,granial and graniol.